Simulation study on the jet formation and penetration capability of hypervelocity double-layer liner shaped charges. (March 2020) - Xie, J W; Wang, H F; Zheng, Y F; Geng, B Q; Ge, Ch
Abstract: The jet formation and penetration capability of hypervelocity double-layer liner shaped charges (HDLLSCs) against rolled homogeneous armor (RHA) targets are investigated by numerical simulation. The HDLLSCs with different cone angle and relative position of disc are simulated to investigate the influence of these parameters on penetration capability and compare with a traditional conical shaped charge (CSC). The simulation results show that, the tip velocity of the jet formed by HDLLSCs with a tantalum disc is lager by 6.8% compared with that formed by the CSCs. The three stages of jet formation for HDLLSC including converge, formation, and secondary impact are revealed and discussed. The penetration capability of HDLLSCs is influenced by the coupled effect of cone angle and relative position of disc, a larger relative position of disc is more suitable for a large cone angle. In addition, the standoff also has a significant effect on the penetration depth of HDLLSCs, the penetration depth increases from 3.31 charge diameter (CD) to 6.52 CD with the standoff increasing from 1.5 CD to 4.0 CD. Moreover, the penetration depth of the jet formed by HDLLSCs is larger by 18.5% compared with that formed by the CSCs at the standoff of 4.0 CD.